2021
DOI: 10.1161/circinterventions.120.009750
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Classification and Posttreatment Remodeling Characteristics to Guide Management and Follow-Up of Neonates and Infants With Coronary Artery Fistula: A Multicenter Study From the Coronary Artery Fistula Registry

Abstract: Background: Coronary artery fistulas (CAFs) presenting in infancy are rare, and data regarding postclosure sequelae and follow-up are limited. Methods: A retrospective review of all the neonates and infants (<1 year) was conducted from the CAF registry for CAF treatment. The CAF type (proximal or distal), size, treatment method, and follow-up angiography were reviewed to assess outcomes and coronary remodeling. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
0
20
0
3
Order By: Relevance
“…Furthermore, treatment strategies for thrombotic occlusion of the fistula in children are debated, unlike Kawasaki disease, which has been well-described for the management of coronary aneurysm with thrombus. The recent retrospective review of CCAF in neonate and infants [20] showed the usage of thromboprohylaxis; antiplatelets and anticoagulation in 90% of patients post closure. Suboptimal remodeling was also reported in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment strategies for thrombotic occlusion of the fistula in children are debated, unlike Kawasaki disease, which has been well-described for the management of coronary aneurysm with thrombus. The recent retrospective review of CCAF in neonate and infants [20] showed the usage of thromboprohylaxis; antiplatelets and anticoagulation in 90% of patients post closure. Suboptimal remodeling was also reported in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because of excessive cardiac chamber load, elderly patients may develop arrhythmia and congestive heart failure 6 . Another review of CAF in neonates and infants (<1 year) showed that heart failure was noted in 28 of 48 (58%) patients 7 . Due to the abundant blood flow through the fistula, the involved coronary artery often becomes dilated, tortuous, and even develop aneurysms 8 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Another review of CAF in neonates and infants (<1 year) showed that heart failure was noted in 28 of 48 (58%) patients. 7 Due to the abundant blood flow through the fistula, the involved coronary artery often becomes dilated, tortuous, and even develop aneurysms. 8 Any of the three major coronary arteries may be the feeding artery for CAFs, and the fistula varies in curvature and dilation due to the feeding artery and original point.…”
Section: Discussionmentioning
confidence: 99%
“…While largely presumed to be asymptomatic, a recent study showed that a majority of neonates/infants presented with heart failure–type symptoms, albeit many of them had a larger fistula size. 2 Indications for intervention on CAFs have been controversial because many patients are asymptomatic; however, delaying intervention is associated with a significantly greater risk of death preoperatively and an increased risk of morbidity and mortality postoperatively. 3 Therefore, the majority of CAFs are addressed when they are identified.…”
mentioning
confidence: 99%
“…Transcatheter and surgical approaches have been both been used with good success rates; however, the number of neonates undergoing repair by either method remains low. 2 , 4 Here, we present a case of surgical repair of a large CAF in a neonate after an attempted transcatheter closure resulted in iatrogenic tricuspid regurgitation (TR). The institutional review board of Children's Healthcare of Atlanta approved the study protocol and publication of data (approval number: STUDY00001462, date approved: July 18, 2022).…”
mentioning
confidence: 99%